THE EFFECTIVENESS OF BREAST SELF-EXAMINATION DEMONSTRATION EDUCATION ON IMPROVING ADOLESCENTS' KNOWLEDGE AND SKILLS - Wati, Patma; Rianti, Emy; Nurhaeni , Heni (Universitas Airlangga, 2026)
Introduction: Breast cancer is one of the leading causes of death in women in the world and is increasing every year. Breast cancer can be prevented by early detection through Breast self-examination. This study aims to analyze the effectiveness of Breast Self-Examination on improving adolescents' knowledge and skills in the early detection of breast cancer. Method: The research design employed was a quasi-experimental design with a pre-test and post-test approach for both the intervention group and the control group. The sampling technique used was purposive sampling. The respondents selected by the researcher were adolescent girls aged 12–18 years attending a public junior high school in Jakarta. Data collection was conducted through knowledge questionnaires and skill questionnaires administered in April 2025. Data were analyzed using the Wilcoxon Signed Rank Test to assess changes within each group and the Mann-Whitney U Test to compare differences between the intervention and control groups. Result: The test results, using the Mann-Whitney Test on the intervention and control groups, showed an increase in knowledge and skills. The results of the Wilcoxon test on pre-test and post-test were significant at the level of knowledge and skills in adolescents towards early detection of breast cancer, with a p-value <0.05. Conclusion: Educational demonstrations on breast self-examination have been proven effective in improving adolescents' knowledge and skills in the early detection of breast cancer. Health education on breast self-examination is important to be implemented from the adolescent age when menstruation begins as a preventive measure against breast cancer. Keywords: Demonstration, Skills, Knowledge, Adolescent Self-Breast Examination.